Frequency of Severe Postpartum Hemorrhage After Delivery Among Obese Pregnant Women - Humaira, Ayesha; Munwar, Ayesha; Saeed, Amna; Nasim, Noreen; Saeed, Khadija; Yasmin, Safia (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of severe postpartum hemorrhage after delivery among obese pregnant women. Methods: This case series was carried out from 15th December 2015 to 15th October 2016 at Department of Obstetrics & Gynaecology, Nishtar Hospital, Multan. A total of 505 obese pregnant women with gestational age 38–41 weeks and parity ≤ 3 undergone vaginal delivery or elective cesarean section were included. Women with history of hypertension, diabetes, renal disease and pre-eclampsia were excluded. In vaginal delivery women were given prostaglandin E2 vaginal gel 1 gm and the same dose repeated at six hourly intervals for maximum three doses under supervision of consultant. In patients undergone elective caesarean section, caesarean section was done by consultant gynecologist. After delivery, data was collected for severe postpartum hemorrhage. Results: Age range in this study was 25 to 35 years with mean age of 30.318 ± 2.71 years. Mean gestational age was 39.429 ±1.11 weeks and mean BMI was 28.289± 1.06 Kg/m2. Majority of the patients were of 25–30 years 268(53.1%). Parity of 2–3 was present in 69.3% women. Cesarean Section rate was 34.3% and vaginal delivery was 65.7%. Severe PPH was seen in 11.1% obese women. Conclusion: Obese women should be regarded as high risk for PPH.